2020
DOI: 10.1111/jnc.15112
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and therapeutic potential of exosomes in Alzheimer’s disease

Abstract: Exosomes are small extracellular vesicles released by almost all cell types in physiological and pathological conditions. The exosomal potential to unravel disease mechanisms, or to be used as a source of biomarkers, is being explored, in particularly in the field of neurodegenerative diseases. Alzheimer's disease (AD) is the most prevalent neurodegenerative disease in the world and exosomes appear to have a relevant role in disease pathogenesis. This review summarizes the current knowledge on exosome contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 162 publications
(195 reference statements)
0
96
0
1
Order By: Relevance
“…Thus, EVs represent a heterologous population in a given biofluid. Specific isolation of their subpopulations is now an emerging challenge in the field, particularly when the purpose is to use EVs (or their cargo) as potential clinical biofluid markers [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. We could not exclude that distinct EVs interact with each other, resulting in their co-purification [ 30 ].…”
Section: Extracellular Membrane Vesicles and Intercellular Communimentioning
confidence: 99%
“…Thus, EVs represent a heterologous population in a given biofluid. Specific isolation of their subpopulations is now an emerging challenge in the field, particularly when the purpose is to use EVs (or their cargo) as potential clinical biofluid markers [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. We could not exclude that distinct EVs interact with each other, resulting in their co-purification [ 30 ].…”
Section: Extracellular Membrane Vesicles and Intercellular Communimentioning
confidence: 99%
“…Exosomes (EXs): (i) were first characterized about ~40 years ago as a heterogeneous group of cell cytoplasm-derived intracellular micro-particles (MPs) of endosomal origin (also known as ectosomes, shedding vesicles, microvesicles or EMVs); (ii) are variable in their content and morphology, ranging in size from about ~30 to ~100 nm in diameter; (iii) are released by a variety of central nervous system (CNS) cells whose function was originally described as a cytological basis for intercellular signaling and communication (Trams et al 1981 [ 12 ]; Columbo et al, 2014 [ 13 ]; Jiang et al, 2019 [ 14 ]; Mathews and Levy 2019 [ 15 ]; Arbo et al, 2020 [ 6 ]; Martins et al, 2020 [ 16 ]). EXs originated as intracellular endosomes containing intraluminal vesicles (ILV) that fuse with the plasma membrane and empty their plasma membrane-encapsulated cargo.…”
Section: Microvesicle Signaling In Neurodegenerationmentioning
confidence: 99%
“…Recently, one revision of exosomes modulating AD has classified EVs-miRNAs according to the biological fluids collected for the study ( Martins et al, 2020 ). They observed that miRNAs in serum-derived EVs were often upregulated, whereas in plasma, were mostly downregulated.…”
Section: Mirnas As Modulators Of Parkinson’s and Alzheimer’s Diseasesmentioning
confidence: 99%
“…In plasma-derived EVs, miRNA-21, miRNA-23a, miRNA-132, miRNA-193b, and miRNA-338 are downregulated ( Martins et al, 2020 ). Notably, miRNA-23a shows an opposite accumulation between serum and plasma.…”
Section: Mirnas As Modulators Of Parkinson’s and Alzheimer’s Diseasesmentioning
confidence: 99%
See 1 more Smart Citation